Seasonal and spatial variations of marine litter on the south-eastern Black Sea coast. Issue 1 (15th July 2017) - Terzi, Yahya; Seyhan, Kadir
Abstract: The south-eastern Black Sea coast in Turkey was evaluated for marine litter composition and density covering nine beaches during four seasons. The marine litter (> 2 cm in size), was collected from the coast and categorized into material and usage categories. The data analysis showed that plastic was the most abundant litter (≥ 61.65 % ) by count and weight followed by styrofoam and fabric. The marine litter density ranged from 0.03 to 0.58 with a mean (± SD) of 0.16 ± 0.02 items/m 2 by count. Based on weight, it varied between 0.44 and 14.74 g/m 2 with 3.35 ± 1.63. The east side had a higher marine litter density than the west side with significant differences between beaches. The variations due to different seasons were not significant for any beach. The results of this study should provide baseline information about the coastal marine pollution and will assist the mitigation strategies. Highlights: Marine litter was encountered in all surveyed beaches during four seasons. No statistically-significant seasonal variations were detected. 73.55% of total litter items were land based. Plastic was the most abundant litter item in total.